Ethical-Medicolegal Aspects of Installation and Removal of Ventilator in Life Support Efforts for Critical Patients during Covid-19 Pandemic - Syafril Alfian Akbar; Agus Yuda Hernoko; Sutarno (CV WAHANA PUBLIKASI, 2022)
This study aims to analyze the procedures and considerations of medical and medicolegal aspects regarding the installation and removal of the use of ventilators in life support for patients during the COVID-19 pandemic. This study uses a normative juridical legal research method. The results showed that the ethical aspects regarding the installation and removal of the use of ventilators in the effort to support patients’ life during the COVID-19 pandemic were based on an agreement that was born by agreement (therapeutic agreement). The decision to stop or postpone life support therapy for medical treatment for patients is made by a team of doctors who treats patients after consulting a team of doctors appointed by the Medical Committee or the Ethics Committee based on Permenkes Number 37 of 2014. Meanwhile, the legal basis of procedures is in the process of making the installation decision and releasing the use of ventilators in critical patients during the COVID-19 pandemic, referring to the provisions of Permenkes No. 37/2014, Permenkes No. 290 of 2008, and Permenkes RI No. 290 of 2008 concerning the rejection of medical action, which patients and or their closest relatives can do. The legal basis refers to the medicolegal aspect in critical patients when installing and removing a ventilator. It is used as an indicator for determining whether to withdraw life support or withhold life support. Besides being adjusted to the validity of an agreement according to the Civil Code as stipulated in Article 1320, a doctor can initiate to understand a patient in the preparation and legal consequences of this agreement